2021
DOI: 10.1155/2021/6667608
|View full text |Cite
|
Sign up to set email alerts
|

Association between Maternal Dietary Diversity and Low Birth Weight in Central India: A Case-Control Study

Abstract: Low birth weight (LBW) is one of the major public health challenges in India. LBW etiology is multifactorial and linked to multiple determinants, including maternal undernutrition and sociodemographic characteristics. The objective of the present endeavor was to assess how maternal dietary diversity and other sociodemographic factors among marginalized populations are associated with the incidence of LBW. The study was a part of the community-based intervention that aimed to improve maternal and child health i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
8
0
1
Order By: Relevance
“…After adjustment of possible covariates, the present study found that the risk of LBW in the inadequate group was six times higher compared to those born from the adequate dietary diversity score group. Our finding is consistent with that of previous studies ( 12 , 47 , 48 ). In contrast, a recent randomized controlled trial study in India reported that increased consumption of dairy, fruits, and green leafy vegetables before and during pregnancy through a specially formulated snack did not affect birth weight ( 15 ).…”
Section: Discussionsupporting
confidence: 94%
“…After adjustment of possible covariates, the present study found that the risk of LBW in the inadequate group was six times higher compared to those born from the adequate dietary diversity score group. Our finding is consistent with that of previous studies ( 12 , 47 , 48 ). In contrast, a recent randomized controlled trial study in India reported that increased consumption of dairy, fruits, and green leafy vegetables before and during pregnancy through a specially formulated snack did not affect birth weight ( 15 ).…”
Section: Discussionsupporting
confidence: 94%
“…A balanced diet plan should adhere to the dietary recommendations for eating a wide range of foods to obtain vitamins, minerals, carbohydrates, protein, and fat from multiple sources. A variety of cereals, nuts, whole grains, dark green leafy vegetables, organ meats or fish, dairy or dairy products, and their substitutes have been found to be strongly linked to a reduced risk among all causes of death and significantly improve health conditions (Sharma et al, 2021). The findings of this study demonstrated that during pregnancy, most pregnant women failed to maintain their DD guidelines.…”
Section: Discussionmentioning
confidence: 74%
“…In India, as part of the government's healthcare mission, Accredited Social Health Activists (ASHAs) and Anganwadi workers are responsible for measuring the height and weight of babies delivered in the family on the day of the delivery [ 12 ]. The WHO recommends a minimum of four appropriate prenatal and postnatal visits, during which the mother's weight, height, urine, and blood values are measured, she receives a tetanus shot, and additional dietary supplements are prescribed [ 18 ]. In high-priority districts, encouraging community-based education on better mother and baby care as well as home-based treatment for neonate infections might significantly improve newborn survival.…”
Section: Reviewmentioning
confidence: 99%
“…India has a higher weightage of LBWs than the majority of the nations, which is an important public health issue [ 17 ]. Even though the incidence of premature LBW has decreased considerably over the last 10 years, from 20.4% to 16.4%, it continues to be India's major public health problem [ 18 ]. The WHO defines an LBW baby as a baby who weighs below 2500 g at birth [ 19 ].…”
Section: Introductionmentioning
confidence: 99%